The relationship between balance, endurance of core muscles and anaerobic performance in professional basketball players - Aksen Cengizhan, P.; Zorlular, A.; Cobanoglu, G.; Gokdogan, C.; Akaras, E.; Erikoglu Orer, G.; Erikoglu, O.; Kafa, N.; Atalay Guzel, N. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The purpose of this study was to identify relationships between endurance of core muscle, balance and anaerobic performance in basketball players. The muscles of the core help control movements, transfer energy, shift body weight and distribute the stresses of weight-bearing. Balance is the ability to maintain the Center of Gravity (COG) of a body within the base of support with minimal postural sway. Functional movements are highly dependent on the core endurance, and lack of core muscles strength can result in decreased performance and balance. Methods: 20 professional male basketball players (age 17±0.64, height 186.1±6.7, weight 78.9±9.38) were included to this study. Balance was measured using Biodex Biosway™. Endurance of core muscle was evaluated using Mcgill Core Endurance Tests. Anaerobic performance was assessed with running based anaerobic sprint test (RAST). Statistical analysis was performed using the statistical software SPSS. Results: Spearman correlation analysis results showed that there was positive significant correlation between performance and endurance of core muscles (p<0.05). A positive significant relationship was demonstrated between anaerobic performance and balance (p<0.05) and between balance and endurance of core muscles (p<0.05). Discussion: In this study, it was shown that there were statistically significant relationship between core endurance, balance and anaerobic power which effects the athletes performance directly during the match. Therefore, it can be suggested core muscle endurance exercises should be integrated to normal sports specific training programmes in basketball players.